World Reindeer Husbandry: Peoples, Distribution and Challenges - International Centre of Reindeer husbandry, - (International Centre for Reindeer Husbandry, 2009)
This is a fold out 2 sided map of the distribution of reindeer husbandry and peoples and the challenges that they face around the world. This is project of the International Centre for Reindeer Husbandry.